PENGARUH GROWTH DAN LEVERAGE TERHADAP PRICE TO BOOK VALUE DALAM MEDIASI RETURN ON EQUITY DAN DIVIDEND PAYOUT RATIO - Umar Mai, Mochamadi (Ekonomi & Bisnis, 2012)
This study aims to examine the influence of leverage and growth to price book value, and test the mediation return on equity and dividend payout ratio in the causal relationship. The study population was categorized as a company of Jakarta Islamic Index listed on the Indonesia Stock Exchange in the period 2004-2009. Data collection methods used is purposive sampling. Criteria on the sample used, the company must have positive earnings per share and issued financial statements make it possible to determine the variables of the study. Testing of all hypotheses in this study using path analysis with Amos 16.0 package program. Furthermore, some important findings from this study can be stated as follows: 1) growth does not significantly effect the price to book value, 2) leverage has positive and significant effect on the price to book value, 3) return on equity and dividend payout ratio to mediate the influence growth of the price to book value. However, this study found no evidence that the return on equity mediates the effect of leverage on price to book value. Key Word : corporate governance mechanism, value of the firm, boards independent, dividend payout ratio